LEARNING DIALOGUE AS A MEANS OF ACTIVATION OF STUDENTS' COGNITIVE ACTIVITY - Morozov, V.V. (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the essence of a dialogue training, developing of thinking and brisking up the pupils' training-cognitive activity.